P42 Does pulmonary rehabilitation improve exercise capacity and HRQoL in patients with asthma?. (14th November 2013) - Tanner, RJ; Boutou, AK; Raste, Y; Lord, VM; Grillo, LJ; Menzies-gow, A; Hull, J; NS, Hopkinson
Abstract : Introduction: Pulmonary rehabilitation (PR) benefits patients with COPD, however to date there is limited evidence demonstrating its effectiveness in patients with chronic asthma. We hypothesised that patients with asthma would have a significant improvement in exercise capacity and HRQOL following a standard PR programme. The aim of this study was a) to evaluate the impact of PR on exercise capacity and HRQoL in patients with asthma and b) to identify the factors influencing attendance and completion. Methods: We retrospectively audited PR outcome in a cohort of asthmatic patients referred for PR at the Royal Brompton Hospital between 2008 and 2012. Exercise capacity (ISWT), quadriceps maximal volitional contraction (QMVC) and HRQoL (HADS, SGRQ, LINQ, MRC) were assessed before and following PR. Logistic regression analysis was used to determine factors predicting PR completion. Results: 49 patients were referred of whom 25 completed (69.2% female; mean age: 58.7 ± 12.5 years; mean BMI: 31.27 ± 30.1) Completers were moderately obstructed (mean FEV1 % pred: 57 ± 22.9, FEV1 /FVC: 0.63 ± 0.14). 4% of them were current smokers and 8% were ex-smokers (mean history of 11.25pack/yrs). Mean classes attended were 15.3 1 ± 5.4 per patient. There was a significant improvement in QMVC (p = 0.02) and ISWT (p = 0.036) following PR. Other than LINQ score (p = 0.016), there was no improvement in HRQoL measures following PR. Patients with a higher%Fat, according to bioelectrical impedance, were less likely to complete PR once they had been referred. No other statistically significant differences were found between completers and non-completers. Conclusions: Asthmatic patients benefit from attending a PR course in terms of functional capacity and muscle strength. Further prospective studies utilising asthma specific quality of life indices are required to evaluate disease specific benefits of PR and delineate factors predicting successful PR. Does pulmonary rehabilitation improve exercise capacity and HRQoL in patients withasthma?